(untitled) (Intent Research Scientific Journal, 2023)
A retrospective analysis of the medical records of children with a diagnosis of congenital cleft lip and palate in the Department of Maxillofacial Surgery of the Children’s Clinical Hospital was carried out. 3463 children with congenital cleft lip and palate were examined.